2017
DOI: 10.4236/ajps.2017.85068
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Organic Manures and Inorganic Fertilizers on the Growth and Yield of Hybrid Rice (Palethwe-1)

Abstract: We investigated the effect of combining organic and inorganic fertilizers on the growth and yield of hybrid rice (Palethwe-1) in the dry and wet seasons of 2015. Four quantities of inorganic fertilizer were used in the main plot [0%, 50%, 75%, and 100% nitrogen, phosphorus, and potassium (NPK)] based on the recommended amounts of 150 kg N ha ] as part of a split-plot experimental design with three replicates. In both seasons, significant differences in growth parameters including number of tillers hill −1 , so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 20 publications
6
19
0
1
Order By: Relevance
“…The application of organic manure and chemical fertilizers resulted in a considerable increase in panicle length [1]. Similar findings were reported by [39,40].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The application of organic manure and chemical fertilizers resulted in a considerable increase in panicle length [1]. Similar findings were reported by [39,40].…”
Section: Discussionsupporting
confidence: 59%
“…Organic manure and chemical fertilizers boosted rice straw yields [48]. These assumptions are supported by [40,49]. Increasing cropping intensity, the use of modern varieties (high-yielding varieties and hybrids), cultivation of high-biomass-potential crops, nutrient leaching, and unbalanced fertilizer application, with no or little addition of organic manure, have resulted in nutrient mining from the soils.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, T 3 and T 5 also increased the NUE, and lower NUE was noted in sole urea fertilizer treatment during both seasons. Moe et al, (2017) observed that there was no statistically significant difference in the number of tillers generated using I 100 compared with 50% NPK (I 50 ) inorganic fertilizer. However, a larger number of tillers were present in rice plants grown using I 100 compared with 0% NPK (I 0 ) fertilizer.…”
Section: Introductionmentioning
confidence: 91%
“…Integrated Soil Fertility Management (ISFM) is a soil fertility management practice where organic, inorganic (fertilizer), and improved germplasm are combined and adapted to the local conditions resulting in improved nutrient use efficiency and crop productivity (Vanlauwe et al, 2010;Mugwe et al, 2019;Gram et al, 2020). The combined use of organic and Inorganic fertilizers in ISFM resulted in improved productivity of most crops such as maize (Mahmood et al, 2017), Rice (Moe et al, 2017), Tomatoes (Islam et al, 2017), and Yam (Owusu Danquah et al, 2017. The use of ISFM reduces the inorganic fertilizer requirement whiles improving crop productivity.…”
Section: Integrated Soil Fertility Management (Isfm) In the Face Of Climate Changementioning
confidence: 99%